Effect of Different Kinesiotaping Techniques on Nonspecific Chronic Low Back Pain - Kristina Koch; Vilma Dudonienė; Rima Solianik (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Kinesiological taping (KinT) is proposed as one of the techniques that can alleviate back pain. However, no studies have been conducted to demonstrate the most effective kinesiology taping technique for women with chronic non-specific low back pain.